PANDANGAN RASUL PAULUS TENTANG GEREJA PERSEKUTUAN DAN RELEVANSINYA BAGI UMAT KATOLIK STASI SANTO VINSENSIUS A PAULO JENANGAN - Dhani Driantoro Gregorius (Bahasa Indonesia, 2019)
Guild is one model of the Church. In the Church, the faithful communion in one faith, which is Jesus Christ. Model Church reconfirmed by the Council Fathers in the Second Vatican Council. First and foremost is the church fellowship (communion), gathering those who believe (communionfidelium). The church is a church/ association of people united by the Holy Spirit in faith, hope and love. Great Apostle St. Paul laid the foundation why the Church should be aligned. He was very instrumental in spreading Christianity. In the spread of Christianity, he repeatedly stressed the importance ofliving communion of the faithful. According to the St. Paul,fellowship entails living together. In it there is a fairly close relationship braid. There is a shared vision in building a community. A minimum it can be experienced and lived Paul on his missionary journeys are so long and long.